CHOLERA IN MICHOACÀN AND THE FEDERALIZATIÓN OF SANITARY POLITICS IN THE XIX CENTURY (Tzintzun, Revista de Estudios Históricos, 2016)
Cholera was one of the illnesses that provoked the greatest death rates in theworld during the eighteenth century. In Mexico, the states of Chiapas, Tabascoand Oaxaca were the most affected during the period from 1882-1883, andthe people of Michoacan suffered the effects of this illness in 1833 and 1850.In times when the possibility of cholera infection in the country or statealarmed the authorities of Mexico and Michoacan each evaluated specificnecessary personal and public hygiene measures, and these were elaboratedwith the help of medical institutions. In case of the epidemics of 1833 and1850, the sanitary politics in Michoacan were demonstrated in new laws andwith the dissemination of curative methods designed by the Protomedicatoand the Faculty of Medicine and their approved by the state government
Keywords: cholera epidemic; sanitary politics; Protomedicato; Faculty of Medicine; Michoacán; Chiapas; Tabasco; Oaxaca